Robotic Assisted Transvaginal Notes Hysterectomy - Guan, X. (J Minim Invasive Gynecol, 2020)
STUDY OBJECTIVE: To demonstrate a novel approach to transvaginal natural orifice transluminal endoscopic surgery (vNOTES) hysterectomy with bilateral salpingectomy using robotic assistance DESIGN: Video presentation of the surgical procedure. SETTING: University hospital. PATIENTS OR PARTICIPANTS: A 34-year-old G2P1011 with one prior cesarean section and myomectomy complained of dysmenorrhea and chronic pelvic pain and requested for the most minimally invasive form of hysterectomy. INTERVENTIONS: A robotic-assisted transvaginal hysterectomy with bilateral salpingectomy was performed. The surgery began as a conventional transvaginal hysterectomy. An anterior and posterior colpotomy were performed, as which point, a camera was inserted to improve visibility. This allowed for confirmation of suspected adhesions from the patient's surgical history, most notably present in the anterior cul-de-sac between the bladder and uterus. Wristed instruments of the robot, the monopolar scissors and bipolar grasper, were also placed which enabled better navigation in the narrow surgical space. The remainder of the surgery, including the lysis of the dense adhesions, was completed smoothly with robotic assistance. The vaginal cuff was closed with a continuous running v-loc. The pelvis was inspected upon conclusion of the procedure and hemostasis was observed throughout. MEASUREMENTS AND MAIN RESULTS: The surgery was completed in 90 mins without complications. The patient was discharged on the same day. On follow-up, the patient noted that her post-operative pain was significantly less than what she had experienced after her previous myomectomy. CONCLUSION: We showed that robotic-assisted NOTES is a novel and feasible option for transvaginal hysterectomy in indicated patients, particularly those with abnormal pathologies such as dense adhesions. In addition to image-guidance, robotic surgery allows for full articulation of instruments required for this surgery, which improves ease and access over other methods like laparoscopic surgery.